2008
DOI: 10.1098/rstb.2008.0215
|View full text |Cite
|
Sign up to set email alerts
|

Behaviourally mediated crypsis in two nocturnal moths with contrasting appearance

Abstract: The natural resting orientations of several species of nocturnal moth on tree trunks were recorded over a three-month period in eastern Ontario, Canada. Moths from certain genera exhibited resting orientation distributions that differed significantly from random, whereas others did not. In particular, Catocala spp. collectively tended to orient vertically, whereas subfamily Larentiinae representatives showed a variety of orientations that did not differ significantly from random. To understand why different mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 31 publications
(48 reference statements)
1
57
0
Order By: Relevance
“…These camouflage patterns were chosen to instantiate elements of three strategies (BM; edge disruptive with high-contrast patches at the target edge, DE; and surface-disruptive with central highcontrast patches, DC). These have been previously proposed to be effective camouflage for static targets [4][5][6]12]. In addition, four simple variations on these targets were created where the boundary between the high and low-contrast regions within a target was either sharp (SE and SC) or graduated (GE and GC).…”
Section: (A) Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These camouflage patterns were chosen to instantiate elements of three strategies (BM; edge disruptive with high-contrast patches at the target edge, DE; and surface-disruptive with central highcontrast patches, DC). These have been previously proposed to be effective camouflage for static targets [4][5][6]12]. In addition, four simple variations on these targets were created where the boundary between the high and low-contrast regions within a target was either sharp (SE and SC) or graduated (GE and GC).…”
Section: (A) Experimentsmentioning
confidence: 99%
“…At its most basic, it involves coloration that represents a random sample of the background [1]. This type of camouflage functions to avoid the target ever being detected (the first stage of predation), and achieves this simply by increasing the similarity of the target and background [4] so that discrimination between the two is impeded [5].…”
Section: Introductionmentioning
confidence: 99%
“…We showed that humbugs still retained a significant reduction in predation risk even when they were not completely aligned with the background habitat. Indeed, the orientation of an animal against a background can enhance or reduce the individual's crypsis, depending on the alignment of features within the background and body pattern (Webster et al, 2009). It has been shown that in some species of moth, individuals rest in non-random orientations that maximise crypsis with the background (Endler, 1984).…”
Section: Movement and Orientation Of Preymentioning
confidence: 99%
“…It has been shown that in some species of moth, individuals rest in non-random orientations that maximise crypsis with the background (Endler, 1984). Moths will change their orientation to a more cryptic position (Kang et al, 2013) using both visual and tactile information (Kang et al, 2015), thereby reducing predator detection (Webster et al, 2009) and suggesting an adaptive advantage of being in-phase with the background. Our results agree to some extent with the alignment hypothesis: the humbug only suffered increased predation when its patterns were perpendicular (90 deg) to the background, which would be rare in the natural environment.…”
Section: Movement and Orientation Of Preymentioning
confidence: 99%
“…Anti-predator traits can be classified into four broad categories that act at different points along the predation event: (i) traits that reduce detection (e.g. the camouflage of moths against trees, Webster et al 2009), (ii) traits that reduce recognition (e.g. snake-mimicking caterpillars, Hossie and Sherratt 2012), (iii) traits that reduce capture (e.g.…”
Section: Introductionmentioning
confidence: 99%